PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR TEMATIK TEMA 1 ORGAN GERAK HEWAN DAN MANUSIA PADA PESERTA DIDIK KELAS V SDN SAMBIREJO 01 PATI TAHUN AJARAN 2022/2023 - Carolina Hidayah Citra Ningrum; Sukamto Sukamto; Sugiman Sugiman (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
Through observation it was found that the learning activity of students was low with a percentage of 60% so that it affected the cognitive learning outcomes of thematic learning. The percentage of completeness is 40%, teachers only use Theme books and LKS Maestro books, teachers still use the lecture method without any feedback from students, therefore students only listen without any effort to explore their own knowledge and do not learn to think critically in dealing with a problem because the material received in the learning process is more rote. The problem in this study is how to apply the problem based learning model to improve thematic learning outcomes of the theme 1 animal and human movement organs in fifth grade students at SDN Sambirejo 01 Pati in the 2022 academic year /2023. This type of research is Classroom Action Research (CAR). The subject of this research is the cognitive learning outcomes of the fifth grade students of Sambirejo State Elementary School 01 Pati, totaling 8 students. In the first cycle the number of students who completed/achieved the KKM (70) were 3 with a percentage of 37.5%, while there were 5 who did not complete with a percentage of 62.5%. Then in the second cycle there is an increase in student mastery. There are 4 students who complete/achieve the KKM (70) with a percentage of 50% while those who do not complete are 4 with a percentage of 50%. In cycle II the percentage has not reached the set indicator, which is 75%. So that this research was continued in cycle III. The learning outcomes of students in cycle III showed that students who completed/achieved the KKM (70) were 7 children with a percentage of 87.5% while students who did not complete had 1 child with a percentage of 12.5%. The implementation of learning cycle III has met the criteria for learning completeness that has been determined, namely 75% of the total number of students so that classroom action research is stopped in cycle III.